IMPLEMENTASI TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM ZAKAT UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT MISKIN - WINDA AFRIYENIS; ANITA ADE RAHMA; FEBRI ALDI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
This study aims to explain the implementation practices of the distribution of zakat funds by Baznas for poor families in the city of Padang and also to determine the level of significance of the role of the distribution of zakat funds by Baznas to improve the welfare of poor families in the city of Padang. This research was carried out in BAZNAS Padang City. Therefore the author conducted a study to determine the extent of the implementation of information and communication technology used in the collection and distribution of zakat funds by BAZNAS Padang City. The study time is May-October 2018. This research is quantitative descriptive. The results of the study are: to support the operational activities of BAZNAS in Padang City, supported by information and communication technology (simple technology and using internet technology).